Electrical Devices Control System Using Google Assistant: https://doi.org/10.69692/SUJMRD080243 - ORHPOMMA, Sounith; NANHTHAVONG, Bounphong; SOUKHAVONG, Sengthong; NAMPANYA, Bouthsady; LAPHUMKHAM , Somvang (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This paper designed to develop an electrical devices control system using Google Assistant which can control the electrical on/off operations with voice via smartphone to increase the comfort, modernity, and safety from electric shock in the case touching switch on/off buttons directly. The design used the speaker Google home mini as the voice command in English from the smartphone via Google Assistant and direct voice commands; The commands were created on the IFTTT web, the NodeMCU ESP8266 board used to connect between hardware and software, as well as the processing and sending logic commands to change the relay status to control the electric devices and also use the Tuya S08 remote transceiver to control the operation of the air conditioner via Google Assistant. The results of the design and experiments showed that the system can control the electrical equipment as according to the goals and objectives set, including lights, fan, and air conditioner. Blynk APP and Google assistant can control the turn on/off the device at anywhere and anytime. in terms of system mobile must be connected to the Internet. For control with the Google home mini speaker only (without a smartphone) can be controlled at a distance of 10 meters and (also dependenting on the level of the sound that we order. In addition, in the case of air conditioning control, the Tuya S08 transmitter can be placed up to 8 meters away from the air conditioner to be controlled. The results showed that designed systems are more likely to be applied to provide comfort, safety and enable people who are unable to help themselves to walk around to turn on/off electrical devices such as the elderly or disabled person.